2019
DOI: 10.18506/anemon.506539
|View full text |Cite
|
Sign up to set email alerts
|

Algılanan Liderlik Tarzının Tükenmişlik Düzeyine Etkisi: Çanakkale Otel İşletmelerinde Bir Araştırma

Abstract: Bu araştırmanın temel amacı çalışanların otel yöneticilerinde algıladıkları liderlik tarzlarının tükenmişlik düzeylerine etkisini belirlemektir. Araştırmada liderlik tarzları olarak çalışan, üretim ve değişim odaklı liderlik tarzları incelenmiştir. Araştırmanın amacını gerçekleştirmek için Çanakkale ilinde faaliyet gösteren dört ve beş yıldızlı otel çalışanlarına anket uygulanmıştır. Basit tesadüfi yöntemle seçilen otel çalışanlarına toplamda 120 anket dağıtılmış, bunlardan 107 geri dönüş sağlanmış ancak eksik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…It has been pointed out that there may be a relationship between leadership styles and burnout levels. Cinnioğlu (2019) found that change-oriented leadership styles had a significant effect on burnout levels, and production-oriented leadership style had no effect on burnout levels (Cinnioğlu et al 2019). It can be thought that TL is directly related to the behavior style and that there is a relationship between the autocratic leadership dimension and burnout perceptions of leaders who mistreat their followers.…”
Section: Toxic Leadership and Burnoutmentioning
confidence: 99%
“…It has been pointed out that there may be a relationship between leadership styles and burnout levels. Cinnioğlu (2019) found that change-oriented leadership styles had a significant effect on burnout levels, and production-oriented leadership style had no effect on burnout levels (Cinnioğlu et al 2019). It can be thought that TL is directly related to the behavior style and that there is a relationship between the autocratic leadership dimension and burnout perceptions of leaders who mistreat their followers.…”
Section: Toxic Leadership and Burnoutmentioning
confidence: 99%
“…Furthermore, in the study of Erol and Köro glu [65], it is suggested that people working with transformational leaders do not have organizational silence or the intent to participate in every kind of interaction. In two different studies of Cinnio glu et al [66,67] it is also revealed that tourism employees, who work with transformational leaders, do not intend to leave the job. From this result, it can be commented that tourism employees are willing to work with people who have transformational leader characteristics.…”
Section: Related Workmentioning
confidence: 99%